Temperature Dependence of Morphology of Transcrystalline at the Interface of Carbon Fiber and Poly (L‐Lactic Acid) Composite Under a Temperature Gradient Stage. Issue 1 (July 2016) - Zhang, Shengnan; Xu, Duigong; Yang, Wenxiao; Tang, Ping; Bin, Yuezhen
Summary: Thin film of carbon fiber (CF) and poly (L‐lactic acid) (PLLA) composite was prepared by a solution casting technique. Influence of crystallization temperature (Tc ) on morphology of transcrystalline (TC) on the interface between CF and PLLA was investigated under a temperature‐controlled gradient (T‐gradient) stage with temperature ranging from 90 °C to 140 °C. Morphology of TC was observed by polarized optical microscope (POM). Typical TC structure isothermally crystallized on the T‐gradient stage was obtained at the surface of CF when Tc = 111 ∼ 132 °C. As Tc decreased from 132 to 111 °C, nuclei density on the surface of single fiber increased while the thickness of TC layer decreased. Crystallization kinetics of TC was investigated through isothermal crystalization under POM equipped with a temperature‐controlled stage. As Tc decreased, the nucleation rate of TC increased and the growth rate of TC decreased. Furthermore, it revealed that the thickness of TC layer was conducted by the competition between heterogeneous nucleation on the surface of fiber and homogeneous nucleation in the bulk matrix around the fiber. The nucleation rate of TC structure was much higher than homogeneous nucleation rate of spherulites in the bulk matrix when Tc was above 118 °C. In this case, TC had enough space to develop perpendicular to fiber axis. Consequently, thickness of TC layer was larger at higher crystallization temperature. On the contrary, transcrystallization was suppressed by homogeneous crystallization when Tc was below 118 °C due to enhanced nucleation ability of spherulites.